2014
DOI: 10.1128/mcb.00077-14
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mRNA Polyadenylation Requires a Ubiquitin-Like Domain, a Zinc Knuckle, and a RING Finger Domain, All Contained in the Mpe1 Protein

Abstract: Almost all eukaryotic mRNAs must be polyadenylated at their 3= ends to function in protein synthesis. This modification occurs via a large nuclear complex that recognizes signal sequences surrounding a poly(A) site on mRNA precursor, cleaves at that site, and adds a poly(A) tail. While the composition of this complex is known, the functions of some subunits remain unclear. One of these is a multidomain protein called Mpe1 in the yeast Saccharomyces cerevisiae and RBBP6 in metazoans. The three conserved domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 85 publications
(118 reference statements)
5
38
0
Order By: Relevance
“…for RNA binding (Lee and Moore 2014). The same study also showed that Mpe1 is required for the previously established ubiquitination of PAP (Mizrahi and Moore 2000) and for polyadenylation activity.…”
Section: Discussionmentioning
confidence: 53%
“…for RNA binding (Lee and Moore 2014). The same study also showed that Mpe1 is required for the previously established ubiquitination of PAP (Mizrahi and Moore 2000) and for polyadenylation activity.…”
Section: Discussionmentioning
confidence: 53%
“…In other studies MG132 and Bortezomib have been reported to induce mRNA increases through both transcriptional (promoter activation) and post‐transcriptional (mRNA stability) mechanisms (Butler et al, ; Laroia et al, ; Shimizu et al, ). Conversely, MG132 causes defective polyadenylation (Lee and Moore, ) and whilst it has been previously shown that in human tissues, there is a 2.7 kb and a 0.9 kb E11 mRNA species, which differ in their polyadenylation (Martin‐Villar et al, ), there is no suggestion that this is the case in murine tissues. It would be interesting however to examine whether the stabilization of E11 observed here is maintained upon addition of a protein synthesis inhibitor, such as cycloheximide.…”
Section: Discussionmentioning
confidence: 99%
“…The yeast mRNA 3 ′ processing factor CPF contains Mpe1 (Rbbp6 homolog) (see below), Pap1, Pta1 (Symplekin), and the homologs of all six subunits of the mammalian CPSF complex, including Cft1 (CPSF160), Cft2 (CPSF100), Ysh1/Brr5 (CPSF73), Fip1 (Fip1), Yth1 (CPSF30), and Pfs2 (Wdr33) (Zhao et al 1999). Similar to CPSF, multiple CPF subunits have been shown to bind RNA, including Cft1, Cft2, Fip1, Yth1, and Mpe1 (Barabino et al 1997;Zhao et al 1997;Dichtl et al 2002;Lee and Moore 2014).…”
Section: Cpsf and Aauaaa Recognitionmentioning
confidence: 99%
“…This N-terminal region, which is the region of similarity with its yeast homolog, Mpe1, is sufficient for 3 ′ processing activity in vitro. In both proteins, the zinc knuckle and RING domains function in RNA binding, although in neither case does binding appear sequence-specific (Di Giammartino et al 2014;Lee and Moore 2014). Interestingly, knockdown of Rbbp6 in mammalian cells preferentially inhibits the 3 ′ processing of mRNAs that contain AU-rich elements (AREs) in their 3 ′ UTRs (Di Giammartino et al 2014).…”
Section: Rbbp6 and Pas Recognitionmentioning
confidence: 99%
See 1 more Smart Citation